Enzyme inhibitor studies reveal complex control of Methyl-D-Erythritol 4-Phosphate (MEP) pathway enzyme expression in catharanthus roseus - Han, Mei; Heppel, Simon; Su, Tao; Bogs, Jochen; Rausch, Thomas (PLOS ONE, 2013)
In Catharanthus roseus, the monoterpene moiety exerts a strong flux control for monoterpene indole alkaloid (MIA) formation. Monoterpene synthesis depends on the methyl-D-erythritol 4-phosphate (MEP) pathway. Here, we have explored the regulation of this pathway in response to developmental and environmental cues and in response to specific enzyme inhibitors. For the MEP pathway entry enzyme 1-deoxy-D-xylulose 5-phosphate synthase (DXS), a new (type I) DXS isoform, CrDXS1, has been cloned, which, in contrast to previous reports on type II CrDXS, was not transcriptionally activated by the transcription factor ORCA3. Regulation of the MEP pathway in response to metabolic perturbations has been explored using the enzyme inhibitors clomazone (precursor of 5-ketochlomazone, inhibitor of DXS) and fosmidomycin (inhibitor of deoxyxylulose 5-phosphate reductoisomerase (DXR)), respectively. Young leaves of non-flowering plants were exposed to both inhibitors, adopting a non-invasive in vivo technique. Transcripts and proteins of DXS (3 isoforms), DXR, and hydroxymethylbutenyl diphosphate synthase (HDS) were monitored, and protein stability was followed in isolated chloroplasts. Transcripts for DXS1 were repressed by both inhibitors, whereas transcripts for DXS2A&B, DXR and HDS increased after clomazone treatment but were barely affected by fosmidomycin treatment. DXS protein accumulated in response to both inhibitors, whereas DXR and HDS proteins were less affected. Fosmidomycin-induced accumulation of DXS protein indicated substantial posttranscriptional regulation. Furthermore, fosmidomycin effectively protected DXR against degradation in planta and in isolated chloroplasts. Thus our results suggest that DXR protein stability may be affected by substrate binding. In summary, the present results provide novel insight into the regulation of DXS expression in C. roseus in response to MEP-pathway perturbation.